An improved potentiometric method for the measurement of entropy coefficient of lithium-ion battery based on positive adjustment. (November 2022) - Lin, Zhenfeng; Wu, Dongmei; Du, Changqing; Ren, Zhong
Abstract: The entropy coefficient (dU OC /dT) is an important parameter for predicting the heat generation of lithium-ion batteries (LiBs), especially under low-rate conditions. The potentiometric method is generally used to measure the entropy coefficient, which is accurate but time-consuming. Therefore, an efficient and accurate entropy measurement method is urgently needed. In this paper, a fast and accurate improved potentiometric method based on a positive adjustment (PA) is proposed, which reduces the relaxation time to 10 min for the first time. Commercial 18650 lithium-ion cells are used to validate the PA method. Comparing two entropy profiles measured by PA method and conventional potentiometric method (CPM), the result clearly shows that the PA method maintains comparable accuracy to CPM with an average error of ± 0.01 mV/K. Even compared with other new methods proposed in recent years, the PA method still has certain advantages in measurement efficiency.